2022
DOI: 10.3389/fendo.2022.860671
|View full text |Cite
|
Sign up to set email alerts
|

Target Therapy in Thyroid Cancer: Current Challenge in Clinical Use of Tyrosine Kinase Inhibitors and Management of Side Effects

Abstract: Thyroid cancer (TC) is the most common endocrine malignancy. TC is classified as differentiated TC (DTC), which includes papillary and follicular subtypes and Hürthle cell variants, medullary TC (MTC), anaplastic TC (ATC), and poorly differentiated TC (PDTC). The standard of care in DTC consists of surgery together with radioactive iodine (131I) therapy and thyroid hormone, but patients with MTC do not benefit from 131I therapy. Patients with advanced TC resistant to 131I treatment (RAI-R) have no chance of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 129 publications
0
19
0
Order By: Relevance
“…Our results revealed that C15orf48 was highly expressed in PTC and could potentially serve as a biomarker for PTC. PTC is derived from the acinar cells of the thyroid gland, accounting for more than 80% of THCA, and has a relatively low malignancy, while FTC is more aggressive, with more common distant metastasis and vascular invasion (42)(43)(44). Immune scoring reveals specific immune signatures among different subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that C15orf48 was highly expressed in PTC and could potentially serve as a biomarker for PTC. PTC is derived from the acinar cells of the thyroid gland, accounting for more than 80% of THCA, and has a relatively low malignancy, while FTC is more aggressive, with more common distant metastasis and vascular invasion (42)(43)(44). Immune scoring reveals specific immune signatures among different subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Still, many ongoing clinical and preclinical trials with various TKIs are being evaluated in thyroid cancer patients. Food and Drug Administration and European Medicines Agency-approved TKIs for advanced RAIR DTC are presented in Table 4 [ 67 ]. Sorafenib was approved for clinical use after a large multicenter phase III study named DECISION.…”
Section: Treatment Of Ptcsmentioning
confidence: 99%
“…Lenvatinib is an oral multi-kinase inhibitor (VEGFR1–3, PDGFR, FGFR1–4, RET, and c-KIT) [ 8 ]. Several genetic alterations have been identified in ATC molecular pathways, involving VEGFR1, VEGFR2, EGFR, PDGFRα, and KIT that lead to tumor aggressiveness and progression [ 45 , 46 ].…”
Section: Preclinical Rationalementioning
confidence: 99%
“…The most frequent adverse event (AE) in the meta-analysis was hypertension, which was effectively managed by adjusting the dose and giving antihypertensive medication. Proteinuria can be treated with lenvatinib dose reduction and timely withdrawal to prevent renal failure [ 8 , 76 ]. It is still unclear whether lenvatinib played a role in the deaths of two patients who had pneumothorax-related AE and three patients who had severe hemoptysis in the pooled meta-analysis [ 81 ].…”
Section: Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation